Model Pengumpulan dan Pendistribusian Dana Infaq sebagai Instrumen Pemberdayaaan Ekonomi Umat (Studi Kasus di Yayasan Nurul Ashri Yogyakarta) - Sugianto, Sugianto; Aminuddin, Aminuddin; Wahyu Wibowo; Hikmah Endraswati (Yayasan Literasi Sains Indonesia, 2025)
This study aims to analyze the model of collecting and distributing infaq funds at the Nurul Ashri Foundation Yogyakarta as an instrument for economic empowerment of the people. The focus of the article is to find out the model of collecting infaq of the Nurul Ashri Foundation, the distribution of infaq funds, and the economic empowerment of the ummah through infaq funds. This article uses a qualitative method with a field approach, where the researcher goes directly into observing and interacting with the subject to understand the phenomenon discussed. The research sample consisted of employees of the Nurul Ashri Foundation, Secretary, Treasurer, and Division Coordinator. Data was collected through observation, interviews, and documentation to gain an in-depth understanding of the collection and distribution of infaq funds at the Nurul Ashri Yogyakarta Foundation. Data analysis is carried out through four stages: collection, reduction, presentation, and drawing conclusions. This study concludes that the Nurul Asri Mosque develops a model of infak collection with social, digital, and transparent approaches, which increases public participation and trust. The Nurul Ashri Foundation distributes infak funds for educational, social, and religious purposes, with programs such as vegetable wholesale and educational scholarships that have a positive impact. In addition, infak funds are used for economic empowerment through borewell programs, skills training, entrepreneurship, and pre-marriage classes that strengthen the capacity of individuals and families.